Front Cover: Oxidative Dehydrogenation of Cyclohexane by Cu vs Pd Clusters: Selectivity Control by Specific Cluster Dynamics (ChemCatChem 5/2020). Issue 5 (4th March 2020) - Halder, Avik; Ha, Mai‐Anh; Zhai, Huanchen; Yang, Bing; Pellin, Michael J.; Seifert, Sönke; Alexandrova, Anastassia N.; Vajda, Stefan
Abstract : The Front Cover shows nanocrystalline diamond‐supported, partially oxidised Cu and Pd clusters catalysing the oxidative dehydrogenation of cyclohexane. In their Full Paper, Avik Halder, Mai‐Anh Ha et al found that the selectivities that they exhibit are markedly different: while Pd produces benzene, Cu produces cyclohexene, and the root of the selectivity is found to be in the specific structural and redox dynamics of the cluster ensembles in reaction conditions. More information can be found in the Full Paper by A. Halder, M.‐A. Ha et al. on page 1307 in Issue 5, 2020 (DOI: 10.1002/cctc.201901795 ).